Croatia : libraries, archives and museums - Horvat, Aleksandra knjižničarka; Kolanovic, Josip; Zgaga, Višnja (2009)
This entry provides a short historical overview of the oldest writing systems, manuscripts, and books in Croatia. It describes the emergence of the first libraries, archives, and museums from the ninth to the twentieth centuries followed by a description of the present-day situation in the information professions, including legislation regulating the field, the most important libraries, archives and museums, professional associations, professional education, and continuing professional training. The conclusion discusses examples of present-day cooperation between information institutions.
Enciklopedijski članak.
ENG